Microfluidic-prepared, monodisperse, X-ray-visible, embolic microspheres for non-oncological embolization applications. Issue 19 (1st September 2020) - Beh, Cyrus W.; Fu, Yingli; Weiss, Clifford R.; Hu, Charles; Arepally, Aravind; Mao, Hai-Quan; Wang, Tza-Huei; Kraitchman, Dara L.
Abstract : A multi-nozzle device incorporating pseudo-check valves rapidly generates monodisperse, spherical microbeads, impregnated with X-ray contrast agents, suitable for targeted embolic therapy. Abstract : Embolotherapy using particle embolics is normally performed with exogenous contrast to assist in visualization. However, the exact location of the embolics cannot be identified after contrast washout. We developed a novel, pseudo-check valve-integrated microfluidic device, that partitions barium- impregnated alginate from crosslinking solution, thereby preventing nozzle failure. This enables rapid and continuous generation of inherently X-ray-visible embolic microspheres (XEMs) with uniform size. The XEMs are visible under clinical X-ray and cone beam CT both in vitro and in vivo . In particular, we demonstrated the embolization properties of these XEMs in large animals, performing direct intra- and post-procedural assessment of embolic delivery. The persistent radiopacity of these XEMs enables real-time evaluation of embolization precision and offers great promise for non-invasive follow-up examination without exogenous contrast. We also demonstrated that bariatric arterial embolization with XEMs significantly suppresses weight gain in swine, as an example of a non-oncological application of embolotherapy.